HEAT TRANSFER AS A DETERMINING FACTOR IN THE THERMAL PERFORMANCE OF SEMARANG CATHEDRAL - Sulastri Mahmudi; Safitri N.A (JoDA Journal of Digital Architecture, 2026)
Semarang Cathedral is a historic building that increasingly faces challenges in maintaining thermal efficiency amid climate change and rapid urbanization. This study aims to examine the role of heat transfer as a key factor in shaping the thermal performance of buildings using a quantitative approach. Both experimental and numerical methods were employed, involving direct measurements of the surface temperature, relative humidity, and solar radiation intensity across three primary spatial zones: the nave, transept, and altar. Field data were recorded over a 30-day monitoring period using a MAX6675 K-type thermocouple temperature sensor and an LR8432 heat flow logger, with measurements taken at 10-minute intervals. The heat transfer mechanisms, namely conduction, convection, and radiation, were evaluated using Fourier’s law and Nusselt number correlations to estimate the overall heat transfer coefficient. The analysis shows that the plastered brick walls exhibit an average thermal conductivity of 0.65 W/m·K and contribute to a reduction in indoor air temperature of approximately 18.3% relative to outdoor conditions. These results indicate that wall material characteristics and thickness play a decisive role in maintaining the thermal stability within a building. The findings of this study provide a quantitative basis for formulating energy conservation strategies for historic buildings in tropical climates.